Biological relevance of colony morphology and phenotypic switching by Burkholderia pseudomallei - Narisara Chantratita (2018)
Melioidosis is a notoriously protracted illness and is difficult to cure. We hypothesize that the causative organism, Burkholderia pseudomallei, undergoes a process of adaptation involving altered expression of surface determinants which facilitates persistence in vivo and that this is reflected by changes in colony morphology. A colony morphotyping scheme and typing algorithm were developed using clinical B. pseudomallei isolates. Morphotypes were divided into seven types (denoted I to VII). Type I gave rise to other morpliotypes (most commonly type II or III) by a process of switching in response to environmental stress, including starvation, iron limitation, and growth at 42°C. Switching was associated with complex shifts in phenotype, one of which (type I to type II) was associated with a marked increase in production of factors putatively associated with in vivo concealment. Isogenic types II and III, derived from type I, were examined using several experimental models. Switching between isogenic morphotypes occurred in a mouse model, where type II appeared to become adapted for persistence in a low-virulence state. Isogenic type II demonstrated a significant increase in intracellular replication fitness compared with parental type I after uptake by epithelial cells in vitro. Isogenic type III demonstrated a higher replication fitness following uptake by macrophages in vitro, which was associated with a switch to type II. Mixed B. pseudomallei morphologies were common in individual clinical specimens and were significantly more frequent in samples of blood, pus, and respiratory secretions than in urine and surface swabs. These findings have major implications for therapeutics and vaccine development. Copyright © 2007, American Society for Microbiology. All Rights Reserved.